2020
DOI: 10.1111/apt.15823
|View full text |Cite
|
Sign up to set email alerts
|

Letter: low population mortality from COVID‐19 in countries south of latitude 35° North supports vitamin D as a factor determining severity. Authors’ reply

Abstract: LINKED CONTENTThis article is linked to Rhodes et al and Mansur papers. To view these articles, visit https://doi.org/10.1111/apt.15777 and https://doi.org/10.1111/apt.15820.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 10 publications
(8 reference statements)
1
11
0
1
Order By: Relevance
“…COVID-19 confirmed cases and mortality rate in some European countries were reported to be negatively correlated with the mean vitamin D level ( Hastie et al, 2020 ; Ilie et al, 2020 ). The same association was also been observed in countries 35 degrees south of latitude ( Mansur, 2020 ; Rhodes et al, 2020 ). Further, lower vitamin D levels were linked to higher mortality, and vitamin D supplementation could reduce the mortality rate of COVID-19 patients ( Grant et al, 2020 ).…”
Section: Introductionsupporting
confidence: 78%
“…COVID-19 confirmed cases and mortality rate in some European countries were reported to be negatively correlated with the mean vitamin D level ( Hastie et al, 2020 ; Ilie et al, 2020 ). The same association was also been observed in countries 35 degrees south of latitude ( Mansur, 2020 ; Rhodes et al, 2020 ). Further, lower vitamin D levels were linked to higher mortality, and vitamin D supplementation could reduce the mortality rate of COVID-19 patients ( Grant et al, 2020 ).…”
Section: Introductionsupporting
confidence: 78%
“…Therefore, initially, PubMed and Google Scholar were searched for "COVID-19" AND "Vitamin D" (date range, 2020, omitting citations and patents, no language limitations). Repeated searches confirmed the growing interest in the hypothesis that vitamin D deficiency may play an important role in the COVID-19 pandemic (3,10,12,19,25,110,(112)(113)(114)(115)(116)(117)(118)(119)(120)(121)(122)(123)(124)(125)(126)(127) From May 2 to May 19, Google Scholar hits increased from 49 to 88 and PubMed hits increased from 17 publications to 32. By June 16, the Google Scholar search retrieved 158 possible references and the PubMed publications on the topic had increased to 69.…”
Section: Methods: Literature Searchmentioning
confidence: 70%
“…Vitamin D also helps prevent viral infections from progressing to pneumonia by tightening cell junctions (19,28,165,172) And, vitamin D's influence on the coagulation pathway decreases risk of acute respiratory distress syndrome as it decreases thrombosis risks (114,127,157,162,169,173). Therefore, correcting vitamin D deficiency might help prevent COVID-19 illness AND help limit complications when prevention is unsuccessful (25,28,114,169).…”
Section: How Vitamin D May Decrease Serious Covid-19-associated Complmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, many observational studies have reported on risk factors for COVID-19. A recent genome-wide association analysis (GWAS) has implicated that blood group A patients had a higher risk of severe COVID-19 than other blood types [ 3 ], while other studies have found associations between vitamin D levels/latitude, and Bacille de Calmette et Guérin (BCG) vaccine and mortality to COVID-19 [ 4 ]. Based on the results of these studies, shall we tell our blood group A patients to stay home or tell everyone to take vitamin D or get vaccinated with BCG?…”
mentioning
confidence: 99%